Dioscorea alata L anthocyanin extract methanol as a sensitive pH active compound. Issue 1 (April 2021) - Safitri, E; Humaira, H; Nazaruddin, N; Susilawati, S; Murniana, M; Md Sani, N D
Abstract: Anthocyanin from Dioscorea alata L has been successfully extracted using a methanol solvent and has been tested for its sensitivity to pH changes using a UV-Vis spectrophotometer in citrate and phosphate buffer solutions. The extracted anthocyanin showed positive flavonoid and phenol tests. The total yield of crude extract was 1.63% that is related to 3.34 x10 −7 M or 16.72 mg/kg dried sample. The maximum absorption against citrate buffer is at a wavelength of 600 nm with a linear range toward pH 4 to 8, sensitivity = 0.121 and R 2 = 0.98. Furthermore, the maximum absorption for phosphate buffer occurs at a wavelength of 590 nm that has a response linear in the range of pH 6 to 8 and sensitivity = 0.296 (R 2 = 0.97) The optimum concentration of citrate buffer is 0.1M with a linear pH of 4-8 and sensitivity = 0.121 (R 2 = 0.98). The optimum buffer concentration for both citrate and phosphate buffer solutions were reached at 0.1M and 0.075 M, respectively. The extracted anthocyanin showed stable response properties against citrate and phosphate buffer for 140 minutes during the test period. This anthocyanin is potential to be used as an active substance to developed optical pH sensors and biosensors based on the determination of pH change.